Population genetic structure and implication for adaptive differentiation of the snail (Gastropoda, Provannidae) in deep‐sea chemosynthetic ecosystems - Zhang, Yu; Cheng, Jiao; Sha, Zhongli; Hui, Min (Zoologica scripta, 2024)
The snail Provanna glabra is a dominant species inhabiting both hydrothermal vents and cold seeps of the Northwest Pacific Ocean. The genetic diversity and population structure of the snail from the hydrothermal vents of Okinawa Trough and a methane seep in the South China Sea were investigated using mitochondrial cytochrome c oxidase subunit I (COI) and genome‐wide single nucleotide polymorphisms (SNPs). A total of 28,805 SNPs were screened based on 2b‐RAD sequencing. Substantial genetic differences between vent and seep populations were identified based on the two datasets with FST = 0.753 (COI) and FST = 0.109 (SNPs), respectively. The results of phylogenetic tree, ADMIXTURE and principal component analysis jointly supported the population differentiation. Outlier detection confirmed the local adaptation of P. glabras populations, and the annotation of these outliers revealed that they were closely associated with processes of signal transduction, immunity, DNA repair, transposable elements and biological development. The genetic divergence observed between hydrothermal vent and methane seep P. glabra populations might be induced by the geographic barrier, limited dispersal ability and natural selection imposed by local environmental pressures from different deep‐sea habitats, e.g. chemical composition, temperature and microbes. These results provide a genetic basis for the microevolution of snails inhabiting deep‐sea chemosynthetic ecosystems.